Если желания не сбудутся: [роман] / Алла Полянская - Полянская Алла (От ненависти до любви, 2017)
Экземпляры: (20171003) / Инвентарный номер: 40012 / Цена: / Сис.шифр: Р2 / Авт.знак: П 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6